Examples Non-Examples Technique to Improve Students’ Writing Skills at SMK Islam Kunjang - M. Syaichul Muchyidin (Universitas Pendidikan Mandalika, 2023)
SMK Islam Kunjang is one of vocational high schools in Kunjang district. SMK Islam Kunjang is a relatively developing school in any things; such as the system of administration, relation, or teaching methodology or technique, because it runs for about 14 years old. SMK Islam Kunjang is located suburbs. Absolutely, most students were less in spirit to study more over English. The teacher has been trying to determine the technique in teaching especially teaching writing. The students’ writing was poor. One of the problems was the technique used. Examples Non-Examples technique is one of the cooperative learning strategies that employ images and videos connected to fundamental skills and encourages students to be more creative and engaged in developing their own ideas about the subject that they are observing. In this study, eleventh-grade students at SMK Islam Kunjang in the academic year 2022–2023 were asked to write descriptive texts with examples and without examples to see if this improved their writing abilities. Action research in the classroom is the methodology (CAR). The tools were an observational study, a questionnaire, and a test. This study focused on TKJ 1's eleventh grade, which had 45 pupils. The results showed that the average student in cycle one was 70.80%, whereas the average student in cycle two was 81.66. According to the means of cycles one and two, there was a considerable improvement from 77.78 to 81.66 and 70.80% to 89.68% of students passing the indicator of success, respectively. Additionally, pupils showed higher interest in learning how to write descriptive texts. Therefore, it is advised that students use the examples-not-examples strategy to improve their writing, particularly in descriptive texts.